2011
DOI: 10.1124/jpet.110.177675
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil and Ozagrel in Combination Show Neuroprotective Effects on Cerebral Infarction after Murine Middle Cerebral Artery Occlusion

Abstract: Rho kinase (ROCK), one of the serine/threonine kinases, is involved in pathologic conditions, and its activation causes neuronal cell death. Fasudil, a selective ROCK inhibitor, has been reported to cause increased cerebral blood flow (CBF) in the ischemic brain and protect against neuronal cell death by inhibiting ROCK. Ozagrel, a thromboxane A 2 synthase inhibitor, inhibits platelet aggregation and causes vasodilatation, thereby increasing CBF in cerebral thrombosis. The present study evaluates the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Because the half-life of fasudil is very short (9.3 min at 10 mg/kg i.p. in mice) [40], the time points 0, 10, 30 and 60 min were selected for analysis (n = 2 CEA424-SV40 TAg and n = 1 WT animal per time point) (Figure 3 A ). The parent drug was detected in liver tissue already 10 min after administration of the compound (Figure 3 B ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the half-life of fasudil is very short (9.3 min at 10 mg/kg i.p. in mice) [40], the time points 0, 10, 30 and 60 min were selected for analysis (n = 2 CEA424-SV40 TAg and n = 1 WT animal per time point) (Figure 3 A ). The parent drug was detected in liver tissue already 10 min after administration of the compound (Figure 3 B ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Rho/ROCK signaling pathway plays important roles in various cardio-cerebral vascular diseases through its cell-mediated signal transduction system (Koumura et al 2011;Raad et al 2012;Villar-Cheda et al 2012;Inan and Büyükafşar 2008;Fukata et al 2001;Tcherkezian and Lamarche-vane 2007;Harvey et al 2010;Gao et al 2013;Yan et al 2015). Previous studies had shown that, a number of abnormal activations of the Rho/Rock signaling pathway are present in the endothelium following cerebral ischemia, finally resulting in endothelial dysfunction and microcirculatory disturbance (Gibson et al 2014;Takemoto et al 2002;Yagita et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The Rho/Rho-kinase (Rho-associated kinases, ROCK) signaling pathway is one of the most widely studied cell signaling pathways recently that plays important roles in the pathogenesis of several nervous system disorders, such as stroke (Koumura et al 2011), Alzheimer's disease (Raad et al 2012), Parkinson's disease (Villar-Cheda et al 2012), and chronic pain (Inan and Büyükafşar 2008). A wide range of functions have been reported for this pathway, both in the normal nervous system and in brain pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of RhoA activity also reduces cerebral infarction in focal ischemia models (Kilic et al, 2010; Koumura et al, 2011; Yamashita et al, 2007), and prevents tau hyperphosphorylation and p25/CDK5 increase after global cerebral ischemia (Castro-Alvarez et al, 2011). The present study provides new information about upregulation of the GEF-H1 activity, a key upstream regulator of the RhoA activity after brain ischemia.…”
Section: Discussionmentioning
confidence: 99%